Evaluation of FNAC of head and neck swellings: a retrospective study - Sangavi, Arvind Kumar B.; Itagi, Inder Raj; Choudhari, Suhas Y.; U., Venkatesh (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: Neck swellings are one of the commonest clinical presentations encountered by the practicing physicians. Hence; we undertook the present study to assess the incidence and nature of various head and neck swellings by FNAC. Methods: The present study included evaluation of data of all the patients that underwent FNAC for various head and neck swellings. A total of 100 patients were included in this study in which FNAC was performed with lesions in the head and neck regions in the otorhinolaryngology, pediatric, and surgery departments. Cleaning of the area, to be aspirated, was done and a 23‑gauge needle with syringe and trocar was inserted at convenient angles to the lesions and multiple hits was made within the lesion, with sufficient negative pressure; the needle was removed and the pressure was applied to the area of aspiration to avoid bleeding or hematoma formation. Results: Majority of the patients with head and neck swellings belong to the age group of 21 to 30 years. Only 6 and 4 patients were having age of 51 to 60 years and 61 years and above respectively. Out of 100 patients, 36 were males and 64 were females. In a total of 54 patients, diagnosis of inflammatory lesion was made while in case of 34 and 12 patients; diagnosis of benign and malignant lesions was made respectively. Conclusions: Most of the swellings occurring in the head and neck region are inflammatory in nature and affect females more frequently than males.